A microscopic, non-equilibrium, statistical field theory for cosmic structure formation - Bartelmann, Matthias; Fabis, Felix; Berg, Daniel; Kozlikin, Elena; Lilow, Robert; Viermann, Celia (New journal of physics, 2016)
Building upon the recent pioneering work by Mazenko and by Das and Mazenko, we develop a microscopic, non-equilibrium, statistical field theory for initially correlated canonical ensembles of classical microscopic particles obeying Hamiltonian dynamics. Our primary target is cosmic structure formation, where initial Gaussian correlations in phase space are believed to be set by inflation. We give an exact expression for the generating functional of this theory and work out suitable approximations. We specify the initial correlations by a power spectrum and derive general expressions for the correlators of the density and the response field. We derive simple closed expressions for the lowest-order contributions to the nonlinear cosmological power spectrum, valid for arbitrary wave numbers. We further calculate the bispectrum expected in this theory within these approximations and the power spectrum of cosmic density fluctuations to first order in the gravitational interaction, using a recent improvement of the Zel’dovich approximation. We show that, with a modification motivated by the adhesion approximation, the nonlinear growth of the density power spectrum found in numerical simulations of cosmic structure evolution is reproduced well to redshift zero and for arbitrary wave numbers even within first-order perturbation theory. Our results present the first fully analytic calculation of the nonlinear power spectrum of cosmic structures.
Gesehen am 15.09.2017